Equity of referrals to type 2 diabetes rehabilitation in a universal welfare state - Anne Mette Bender; Ina Tapager; Henrik Brønnum-Hansen; Ingelise Andersen; Charlotte Glümer; Karsten Vrangbæk (Elsevier, 2022)
Objective: Despite aims of equal access to treatment and care in the Nordic countries, marked socioeconomic inequality in the development of type 2 diabetes (T2D) complications persists. The study purpose was to estimate the associations of individual socioeconomic position and deprivation at the general practitioner (GP) level with referrals to T2D rehabilitation.Research Design and Methods: In 2015-2018, 3390 people affiliated with 432 primary GPs living in the municipality of Copenhagen were identified through registry data as newly diagnosed with T2D. Of these, 656 (19%) individuals were referred to municipal rehabilitation services in 2015-2021. Individual socioeconomic position was measured by education, income, and employment. The Danish Deprivation Index (DADI) was used as a measure of GP-level deprivation. Results: Patients were more likely to be referred to municipal rehabilitation if they had low vs. high income (hazard ratio (HR) 2.87 [women], 1.64 [men]), were not employed vs. employed (HR 1.95 [women], 1.23 [men]) and were affiliated with GPs with a low vs. very high level of deprivation (HR 7.63 [women], 4.30 [men]). The results suggest that GPs practice proportionate universalism by allocating treatment to lower socioeconomic individuals in likely higher need of care. However, the overall HR for referrals was lower among GPs with more deprived patient populations, indicating unequal treatment of all citizens, which conflicts with the aims of general universal health care. Inequality in rehabilitation healthcare services must be further addressed and investigated to prevent exacerbating health disparities.